(untitled) (Research, Society and Development, 2022)
HIV is the causative agent of the Acquired Immunodeficiency Syndrome (AIDS), the control of the disease is possible due to the treatment with Antiretroviral Therapy - ART, which prevents viral replication and helps in the reconstitution of the immune system, and must be carried out early and not discontinued at any time during the treatment. The Pharmacist is extremely necessary, collaborating in the planning, evaluation and distribution of free medicines to patients. This article aims to expose the importance of Pharmaceutical Assistance in understanding information about antiretroviral treatment in patients with HIV/AIDS in Brazil and its contribution at the time of adherence. This is an integrative review of the literature in which BVS (Virtual Health Library), Google Scholar, and SciELO (Scientific Electronic Lirary Online) databases were consulted, using the descriptors: Adherence; Pharmaceutical care; Antiretroviral Therapy; Acquired immunodeficiency syndrome. The following inclusion criteria were established: articles available in full, in Portuguese and English, from 2012 to 2022 with free access and that had an affinity with the theme. 150 research papers were found in the databases. Of these, 16 were considered for the study. Despite the relevance of the topic, few current articles report the role of pharmacists in relation to the use of antiretrovirals, where only 6 were fully covered. In short, pharmaceutical care aimed at people with HIV/AIDS is relevant, since this professional helps in the correct use of ART, monitoring the treatment, attending to this patient, establishing a relationship of safety and care.